Instrumental Occlusal Analysis in Migraine Patients: A Quantitative Cross Sectional Study - Zokaris Nikolaos; Greven Marcus; Naoumis Dimitrios; Tzakis Michail; Mitsikostas Dimos Dimitrios; Psarras Vasileios (Wiley, 2024)
ABSTRACT Objectives This study aimed to investigate possible differences of functional occlusal variables between a group of migraine patients (MG) and a control group (CG). Materials and Methods Each group included 50 individuals. Instrumental functional analysis and digital occlusal analysis were performed. Variables examined were condylar displacement from a reference position to maximum intercuspation; angular difference between the steepness of the articular eminence and the contra‐lateral canine guidance; and angular difference between the steepness of the articular eminence and the ipsilateral central incisor guidance and occlusal plane inclination. Self‐reported grinding and occlusal index were also investigated. Results There were statistically significant differences in the extent of retral condylar displacement assessed both clinically [MG: 0.49 mm (SD 0.67 mm), CG: 0.29 mm (SD 0.27 mm), p = 0.012] and digital‐mechanically [MG: 1.53 mm (SD 0.95 mm), CG: 0.9 mm (SD 0.66 mm), p = 0.001], the angular difference between the steepness of the articular eminence and the contra‐lateral canine guidance [MG: 13.11° (SD 8.33°), CG: 9.47° (SD 7.08°), p = 0.021 and MG: 12.94° (SD 8.71°), CG: 9.44° (SD 8.70°), p = 0.017], and the occlusal plane inclination [MG: 11.16° (SD 4.66°), CG: 9.09° (SD 4.37°), p = 0.024]. Self‐reported grinding (MG: 39/50, CG: 12/50, p < 0.001) and occlusal index [MG: 1.92 (SD 0.46), CG: 0.21 (SD 0.66), p < 0.001] were also significantly higher in migraineurs. Conclusions Articular and occlusal structures could play a role in migraine and thus should be considered in an interdisciplinary approach.